Cowpox virus infection from ped rat - Uwe Wollina; Gesina Hansel; Jacqueline Schönlebe (Our Dermatology Online, 2018)
Cowpox virus belongs to the genera of double-stranded DNA orthopoxviruses. Although it has a low pathogenicity for humans, transmission from infected animals like rodents and cats to humans has been observed. We report on a 19-year-olf female patient who presented with oculo-cutaneous ulcerations and lymphadenopathy, fever and general malaise. Detailed medical history, contact to infected pet rats, histopathology, and course confirmed the diagnosis of human cowpox. Human cowpox is rare but seems to be an emerging disease transmitted in most cases by pets to humans. There is yet no specific treatment available.